KERJASAMA EKSPOR CRUDE PALM OIL (CPO) INDONESIA KE NEGARA ITALIA TAHUN 2011-2015 - Yesi Ningsih Paradila; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This paper is a Bilateral Trade study that provides an analysis of the Cooperation of two countries in the fulfillment of needs and achieve their nasal interests. This research is focused on Indonesia Crude Palm Oil (CPO) Exports to Italy from 2011-2015. Crude Palm Oil is the result of processed pulp of palm fruits as vegetable oil which is needed as industrial material and household consumption. Where Indonesia as the world's largest producer of palm oil contributes 51% to the world's palm oil demand and engages in exports to various countries including Italy. This paper used the liberalism perspective written by Adam Smith. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data is gotten and collected from the journal books, the last thesis and then from internet has related to the problems. This research showed that Indonesia and Italy has good relations in all things especially in the trade sector. The purpose of Indonesia in cooperation with Italy is to promote the product of palm indonesia to Italy. Indonesia always faces the increasing of CPO exports to Italy every year, and Italy’s dependence to Indonesia’s CPO for the biofuel and food industries.Keyword: Internasional Corporation, Liberalism Perspective, National Interest, Export Crude Palm Oil